T-Even Bacteriophage-Tolerant Mutants of Escherichia coli B III. Nature of the tet Defect - Hewlett, Martinez J. (1973)
T-even phage-tolerant (tet) mutants of Escherichia coli B are shown to lack the enzyme uridine diphosphoglucose pyrophosphorylase and thus produce nonglucosylated progeny phage deoxyribonucleic acid.